Pengararuh Jenis Media Tanam Hidroponik Agregat dan Electrical Conductivity Larutan Nutrisi Terhadap Pertumbuhan dan Produksi Melon - Ariessandy, Irvan; Triyono, Sugeng; Amien, Elhamida Reskia; Tusi, Ahmad (Jurnal Agricultural Biosystem Engineering, 2022)
This study aims to determine the effect of aggregate hydroponic growing media and EC (Electrical Conductivity) nutrient solution on the growth and production of melon (Cucumis melo L.). This study used a Factorial Completely Randomized Design (RALF) consisting of 2 factors, namely the type of planting medium (cocopeat and husk charcoal) and the EC value (1, 2, 3, 4, 5) mS/cm, each replicated as much as 3 times to obtain 30 experimental units. The results showed that cocopeat was a planting medium that gave the best response to the parameters of fruit weight and sweetness level with an average fruit weight of 2.46 kg, in addition the use of EC 2 mS/cm and EC 3 mS/cm gave the best response to parameters of fruit weight and sweetness level with an average fruit weight of 2.04 kg and 2.05 kg. Based on these results, the use of EC 2 ms/cm was chosen as the best treatment, because it gives maximum results by spending less resources when compared to EC 3 mS/cm.